Pengalaman Guru dalam Menilai Sikap Religius Siswa pada Pembelajaran Matematika: Studi Kualitatif Berbasis Nilai Islam - Jamiat, Ahmad; Remiswal, Remiswal; Khadijah, Khadijah (ALACRITY : Journal of Education, 2025)
This study aims to explore the experiences of mathematics teachers in assessing students’ religious attitudes at SMPN 25 Padang. The research focuses on how teachers understand, implement, and evaluate religious values in mathematics instruction, as well as the challenges they face. A qualitative approach with a phenomenological method was employed. Primary data were collected through in-depth interviews, observations, and documentation, involving Grade VII mathematics teachers as key informants. The findings reveal that teachers possess a strong understanding of religious values such as honesty, responsibility, patience, and discipline, and actively integrate these values into their teaching practices. Assessment is conducted through daily observation, student reflection journals, attitude rubrics, and both self- and peer-assessment. However, teachers encounter challenges related to limited time, subjective judgments, and a lack of standardized instruments. These findings highlight the need for continuous training, peer collaboration, and support from both the school and parents. The study offers important implications for the development of character education based on Islamic values that can be effectively embedded within mathematics instruction.